The Relationship of Interest and Metacognitive Ability through a Project-Based Learning Model on Reaction Rate Materials at Dian Harapan Holland Village Manado School - Miracle Lendo; Soenandar M. T. Tengker; Jeanne Tuerah (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
This research using the PTK (Classroom Action Research) method which aims to be able to find efforts to increase student activities through project-based learning models, to improve cognitive abilities and student learning interests. Learners are educational subjects considered active in shaping their chemistry learning achievement. The subjects this study is students of class XI IPA 2 SMA Dian Harapan Holland Village Manado. The focus of this research is the cognitive ability and learning interest of students. The results showed that the cognitive ability and interest in learning class XI IPA 2 SMA Dian Harapan Holland Village Manado there is an increase marked by an increase in the average score from cycle I to cycle III. There was also an increase in the activity of students. Therefore, the implementation of the Project Based Learning Model (PjBL) can provide a good and positive response for students.